2023
DOI: 10.1038/s41375-023-01826-y
|View full text |Cite
|
Sign up to set email alerts
|

The histone demethylase JMJD2C constitutes a novel NFE2 target gene that is required for the survival of JAK2V617F mutated cells

Abstract: The transcription factor NFE2 is overexpressed in most patients with myeloproliferative neoplasms (MPN). Moreover, mutations in NFE2, found in a subset of MPN patients, strongly predispose for transformation to acute leukemia. Transgenic mice overexpressing NFE2 as well as mice harboring NFE2 mutations display an MPN phenotype and spontaneously develop leukemia. However, the molecular mechanisms effecting NFE2-driven leukemic transformation remain incompletely understood. Here we show that the pro-leukemic his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…For example, it has been shown that modulation of these post-translationally modified splicing factors downstream of mutated JAK2 kinase had an impact on clonal persistence and progression [31]. Similar mechanisms have been explored for epigenetic modifiers such as KDM4C or JMJD2C in JAK2-mutated cells [32,33].…”
Section: Additional Mutationsmentioning
confidence: 98%
“…For example, it has been shown that modulation of these post-translationally modified splicing factors downstream of mutated JAK2 kinase had an impact on clonal persistence and progression [31]. Similar mechanisms have been explored for epigenetic modifiers such as KDM4C or JMJD2C in JAK2-mutated cells [32,33].…”
Section: Additional Mutationsmentioning
confidence: 98%